Humanitarian Assistance in the Minawao Camp Through the Eyes of its Refugees: Perception and Accountability Challenges in A Context of Protracted Displacement - MAGNE, Marie Rosette; HASSANE, Abdoulaye Boureima; AHOLOU, Coffi Cyprien (Journal of Ecohumanism, 2025)
For a decade, the Minawao camp in Cameroon has been hosting Nigerian refugees facing inadequate humanitarian assistance. Drawing on a methodology that combines ethnographic immersion, focus groups, a questionnaire survey and semi-structured interviews with refugees, this study examines refugees’ perception of aid in a crucial context of accountability and refugee legitimacy. The findings reveal a decline in the quality of assistance, non-inclusive camp management, limited understanding of aid mechanisms, and fundamental notions related to refugee status. This situation fosters a sense of non-accountability towards the camp, reducing their engagement in camp activities, despite humanitarian agencies’ efforts to improve living conditions. Refugees are calling for inclusive management and a reorientation of programs toward autonomy, grounded in their real needs and aspirations for a safe return to Nigeria. The study advocates for a revision of accountability practices through increased refugee participation in decision-making processes, promoting more responsible and tailored humanitarian aid, and empowering refugees to take an active role in shaping their futures.